2020
DOI: 10.3390/brainsci10080506
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Type 1 Sialidosis: Clinical Insights from Long-Term Care of Four Unrelated Patients

Abstract: Background: Sialidosis is a rare autosomal recessive disease caused by NEU1 mutations, leading to neuraminidase deficiency and accumulation of sialic acid-containing oligosaccharides and glycopeptides into the tissues. Sialidosis is divided into two clinical entities, depending on residual enzyme activity, and can be distinguished according to age of onset, clinical features, and progression. Type 1 sialidosis is the milder, late-onset form, also known as non-dysmorphic sialidosis. It is commonly characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…These three neurodegenerative conditions are very rare, with an approximate prevalence of 1/5,000,000-1/1,500,000 live births for Sialidosis (OMIM #256550)[ 4 ], 1:100,000–1:200,000 live births for GM1 gangliosidosis (OMIM #230500) [ 5 , 6 ], and from 0.35 to 2.2 per 100,000 births, depending on the geographic area, for NPC (OMIM #257220) [ 7 ]. The mild form of sialidosis Type I, whose clinical presentation is mostly confined to ophthalmologic problems and myoclonus, and the juvenile/adult forms of GM1 gangliosidosis are probably underestimated and likely to be more common than reported [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These three neurodegenerative conditions are very rare, with an approximate prevalence of 1/5,000,000-1/1,500,000 live births for Sialidosis (OMIM #256550)[ 4 ], 1:100,000–1:200,000 live births for GM1 gangliosidosis (OMIM #230500) [ 5 , 6 ], and from 0.35 to 2.2 per 100,000 births, depending on the geographic area, for NPC (OMIM #257220) [ 7 ]. The mild form of sialidosis Type I, whose clinical presentation is mostly confined to ophthalmologic problems and myoclonus, and the juvenile/adult forms of GM1 gangliosidosis are probably underestimated and likely to be more common than reported [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Bou Ghannam AS et al reported a case where no cherry-red spots were observed in the fundus 10. Likewise, Coppola et al observed patients for as long as 30 years and found no cherry-red spots in the fundus 11. Therefore, while cherry-red spots may appear in type I sialidosis, using it to name the disease is imprecise and may mislead clinicians in making early diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, decreased connectivity from the temporal and occipital lobes to the hippocampus and para-hippocampus has also been noted. Moreover, a compromised posterior visual pathway, with extensive involvement of the brain’s posterior part, has been related to cortical blindness in sialidosis I patients ( Lai et al, 2009 ; Sobral et al, 2014 ; Lu et al, 2017 ; Gultekin et al, 2018 ; Hu et al, 2018 ; Coppola et al, 2020 ).…”
Section: Neu1 and Sialidosismentioning
confidence: 99%
“…Type I sialidosis is the less severe form, with a late onset of symptoms ( d’Azzo et al, 2015 ). Typical symptoms of type I sialidosis, also known as cherry-red spot myoclonus syndrome, include progressive visual loss, bilateral cherry-red spots, and myoclonus, and are generally manifested during adolescence ( Coppola et al, 2020 ). Type II sialidosis, in contrast, takes a more severe course and is further subdivided into three subtypes.…”
Section: Introductionmentioning
confidence: 99%